2019
DOI: 10.4274/btdmjb.galenos.2017.20170603015031
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Level of Knowledge on Childbirth and Fear of Childbirth among Pregnant Women

Abstract: Objective: To determine level of knowledge on childbirth among pregnant women and assess the relationship between knowledge on childbirth and fear of childbirth. Methods: This is a cross-sectional study conducted on pregnant women who applied to Sakarya Training and Research Hospital from 15 December 2015 to 15 April 2016. Out of all pregnant women presented to the pregnancy follow-up polyclinic during the study, the study group consisted of 681 women who agreed to take part in the study (56%). A questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
(11 reference statements)
1
3
0
Order By: Relevance
“…It was determined that the mean fear of childbirth score experienced by the pregnant women included in the study was in the range of 0–130 and was at a low level. In addition to moderate birth fear results in the literature 3 , 25 , 26 studies with parallel results with our study 8 , 9 , 11 , 27 , it has been determined that there is a negative and weakly significant relationship between the PBI scores and W-DEQ-A scores of the pregnant women (p=0.023). As the W-DEQ-A scores of pregnant women increase, PBI scores decrease.…”
Section: Discussionsupporting
confidence: 89%
“…It was determined that the mean fear of childbirth score experienced by the pregnant women included in the study was in the range of 0–130 and was at a low level. In addition to moderate birth fear results in the literature 3 , 25 , 26 studies with parallel results with our study 8 , 9 , 11 , 27 , it has been determined that there is a negative and weakly significant relationship between the PBI scores and W-DEQ-A scores of the pregnant women (p=0.023). As the W-DEQ-A scores of pregnant women increase, PBI scores decrease.…”
Section: Discussionsupporting
confidence: 89%
“…A multiple-choice test is suitable for this purpose [ 31 ]. Since no instrument was available in German or related to the German health care system, research groups outside of Germany that have used such a measure were contacted and asked for information on its development [ 25 , 26 ]. However, this information was not available, so a new knowledge test was developed in this study to capture birth-related knowledge.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is unknown what information and knowledge they have. There are only few studies that have objectively measured birth-related knowledge, but they cannot be transferred to the German population [ 25 , 26 , 28 , 29 ]. To address this research gap, this present study developed a German knowledge test assessing young women’s knowledge of childbirth, and test for its relation to childbirth fear and mindset.…”
Section: Childbirth Fear Natural or Medical Mindset Birth-related Kno...mentioning
confidence: 99%
“…22 There is evidence that the care received during the antenatal period and education about birth are important factors affecting fear and anxiety in the antepartum period and better quality antenatal care and education may reduce anxiety in this period. 20,23 "Characteristics of Domestic Violence (CDV) subdimension score is 1.37±0.53" was found to be at a "very poor" level in the present study. Da Cunha Coelho et al found that lack of social support increased violence in their cohort of 828 pregnant women in Brazil.…”
Section: Discussionmentioning
confidence: 46%